The Logistics Infrastructure Network of Belarus and its Universal Applications - Kugan, Svetlana (Management and Administration Journal, 2020)
The effective functioning of the logistics infrastructure is a prerequisite for the modernization of the regional and, as a result, the national economy, the transition to an innovative development path, as well as improving the population living standards. The study of historical patterns and characteristics of the development of logistics will allow us to determine the main directions for improving the activities of the logistics infrastructure and use appropriate management tools. The most important elements of the regional infrastructure are traditionally automobile and rail transport, which ensure republican and international relations of the region.